2016
DOI: 10.1186/s12974-016-0577-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica study model based on chronic infusion of autoantibodies in rat cerebrospinal fluid

Abstract: BackgroundDevic’s neuromyelitis optica (NMO) is an autoimmune astrocytopathy, associated with central nervous system inflammation, demyelination, and neuronal injury. Several studies confirmed that autoantibodies directed against aquaporin-4 (AQP4-IgG) are relevant in the pathogenesis of NMO, mainly through complement-dependent toxicity leading to astrocyte death. However, the effect of the autoantibody per se and the exact role of intrathecal AQP4-IgG are still controversial.MethodsTo explore the intrinsic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 53 publications
2
55
1
Order By: Relevance
“…One study[19] was not included due to lack of normal controls (S1 Fig). Compared with studies in healthy controls, three studies in MS patients showed an association of positivity of anti-KIR4.1[10,11,14] and seven studies, including our own, showed no significant differences[12,13,16,20,21,2729] (Fig 4). The statistical heterogeneity between studies was over 75% and did not allow data pooling to perform meta-analysis.…”
Section: Resultscontrasting
confidence: 45%
See 3 more Smart Citations
“…One study[19] was not included due to lack of normal controls (S1 Fig). Compared with studies in healthy controls, three studies in MS patients showed an association of positivity of anti-KIR4.1[10,11,14] and seven studies, including our own, showed no significant differences[12,13,16,20,21,2729] (Fig 4). The statistical heterogeneity between studies was over 75% and did not allow data pooling to perform meta-analysis.…”
Section: Resultscontrasting
confidence: 45%
“…The studies were developed in the USA (3)[15,16,20], Germany (2)[10,11], France (2)[12,27], Japan (2)[28,29], Israel (1)[14], Italy (1)[21], Spain (1), Switzerland (1)[19], and Turkey (1)[13]. They showed substantial variability in the technical determination of anti-KIR4.1 and control group populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curiously, similar pathology was seen in rats pre‐treated with cobra venom factor, suggesting a complement‐independent mechanism. A related model involved continuous intraventricular infusion of patient‐derived AQP4‐IgG for 7 days by osmotic mini‐pump . Human IgG was seen in brain, spinal cord and optic nerve, with the loss of AQP4 and reactive astrocytes in spinal cord and optic nerve, and demyelination and axonal injury in spinal cord.…”
Section: Passive Transfer Models Of Nmomentioning
confidence: 99%